Sperm mRNAs and microRNAs as candidate markers for the impact of toxicants on human spermatogenesis: an application to tobacco smoking. (June 2015) - Metzler-Guillemain, Catherine; Victorero, Genevieve; Lepoivre, Cyrille; Bergon, Aurélie; Yammine, Miriam; Perrin, Jeanne; Sari-Minodier, Irene; Boulanger, Nicolas; Rihet, Pascal; Nguyen, Cathy
Abstract Spermatozoa contain a complex population of RNAs including messenger RNAs (mRNAs) and small RNAs such as microRNAs (miRNA). It has been reported that these RNAs can be used to understand the mechanisms by which toxicological exposure affects spermatogenesis. The aim of our study was to compare mRNA and miRNA profiles in spermatozoa from eight smokers and eight non-smokers, and search for potential relationships between mRNA and miRNA variation. All men were selected based on their answers to a standard toxic exposure questionnaire, and sperm parameters. Using mRNA and miRNA microarrays, we showed that mRNAs from 15 genes were differentially represented between smokers and non-smokers (p < 0.01): five had higher levels and 10 lower levels in the smokers. For the microRNAs, 23 were differentially represented: 16 were higher and seven lower in the smokers (0.004 ≤ p < 0.01). Quantitative RT-PCR confirmed the lower levels in smokers compared to non-smokers for hsa-miR-296-5p, hsa-miR-3940, and hsa-miR-520d-3p. Moreover, we observed an inverse relationship between the levels of microRNAs and six potential target mRNAs (B3GAT3, HNRNPL, OASL, ODZ3, CNGB1, and PKD2). Our results indicate that alterations in the level of a small number of microRNAs in response to smoking may contribute to changes in mRNA expression in smokers. We conclude that large-scale analysis of spermatozoa RNAs can be used to help understand the mechanisms by which human spermatogenesis responds to toxic substances including those in tobacco smoke.